2016
DOI: 10.20463/jenb.2016.06.20.2.7
|View full text |Cite
|
Sign up to set email alerts
|

GLUT2 proteins and PPARγ transcripts levels are increased in liver of ovariectomized rats: reversal effects of resistance training

Abstract: [Purpose]This study investigated the effects of ovariectomy (Ovx) and 12 weeks of resistance training (RT) on gene expression of GLUT2, the main glucose transporter in the liver, and on PPARγ, a transcription factor known to target GLUT2 expression.[Methods]Forty Holtzman rats were divided into 5 groups: Sham-sedentary (Sed), Sham- RT, Ovx-Sed, Ovx-RT, and Ovx-Sed with hormone replacement (E2). The RT protocol consisted of sessions held every 72 h for 12 weeks, during which the animals performed 4 to 9 vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the present study, we observed that resistance exercise training significantly increases GLUT-2 and decreased AMPK ( Figure 4 ). Other studies have reported that exercise training improves GLUT-2 and AMPK expression in several peripheral tissues [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that resistance exercise training significantly increases GLUT-2 and decreased AMPK ( Figure 4 ). Other studies have reported that exercise training improves GLUT-2 and AMPK expression in several peripheral tissues [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomies of female Holstman rats did not affect liver glycogen levels or phosphoenolpyruvate carboxykinase (PEPCK, the main enzyme in the gluconeogenesis pathway) gene expression, but after E2 replacement the expression was altered (glycogen-increased, PEPCK-decreased) [34]. However, according to another study [35], following the ovariectomy of obese female rats the expression of lipogenic (sterol-regulatory element-binding protein 1c, SREBP-1c; FASN) and adipogenic (PPAR-γ) genes in the liver increased significantly, and administration of exogenous E2 or an ERα agonist (16a-LE2) reduced hepatic expression of SREBP-1c, FASN and PPAR-γ, while an ERβ agonist (8β-VE2) comparably increased PPARγ expression to the same level of mRNA as in non-treated ovariectomized animals [35].…”
Section: Relationship Between Estrogens/estrogen Receptors/aromatase mentioning
confidence: 98%
“…Accordingly, the oscillation of ER expression has great importance for limiting fat deposition in the livers of women of reproductive age, and appropriate HRT in post-menopausal women or after surgical menopause, and has an important role for hepatic metabolism [36]. This protective function of estrogens is mainly attributed to ERα signalling [37] because, as was shown in microarray analysis, male and female ERαKO mice exhibit a fatty liver due to the up-expression of lipogenic genes and down-expression of genes involved in lipid intake [34]. Mice with liver ERα-knockout (LKO) [38] and Gpr30-deficient mice (GPR30; orphan G protein-coupled receptor 30) [39] fed a HFD had increased liver triglycerides and diacylglycerides, and female rather than male mice had significantly lower HDL-C level along with an increase in fat liver accumulation with insulin resistance.…”
Section: Relationship Between Estrogens/estrogen Receptors/aromatase mentioning
confidence: 99%
“…PEPCK mRNA levels in the liver are elevated in ovariectomized rats and arsenic-treated ovariectomized mice, but Tomaz et.al. reported that Pepck expression does not change in the livers of estrogen sulfotransferase ( Est ) transgenic mice or ovariectomized rats ( Khor et al., 2010 , Tomaz et al., 2016 ). Our results are consistent with the former and also with the conclusion that estradiol can suppress hepatic gluconeogenesis in female rats following 21 D of treatment with exogenous estrogen and progesterone ( Matute and Kalkhoff, 1973 ).…”
Section: Discussionmentioning
confidence: 99%